The Canada Health Act and Mental Health and Addiction Services - Erika Dyck (HealthcarePapers, 2025)
The 40th anniversary of the Canada Health Act (CHA) (1985) comes at an auspicious time in healthcare history, having just experienced a major global pandemic that tested both the foundations and the flexibility of Canadian medicare. Several services suffered under the pressure of the pandemic, including mental health. Despite its historic position as a public or charitable service, mental health and addiction care has been pushed to the edges of our publicly funded health system. On this anniversary of the CHA, the author reflects on this historical trajectory by revisiting the origins of medicare and the impact of psychiatric deinstitutionalization.
Keywords: Canada Health Act, mental health, addiction, deinstitutionalization